Grape Seed Proanthocyanidin Extract Inhibits Human Esophageal Squamous Cancerous Cell Line ECA109 via the NF-κB Signaling Pathway - Fangming Guo; Yunhua Hu; Qiang Niu; Yu Li; Yusong Ding; Rulin Ma; Xianhua Wang; Shugang Li; Jianxin Xie (Hindawi Limited, 2018)
Esophageal squamous cell carcinoma is the most common type of squamous cell carcinoma. Grape seed proanthocyanidin extract (GSPE) is considered to exhibit anticancer activity against several different types of cancer. We aimed to determine whether GSPE inhibited esophageal squamous cancerous cells and the possible involvement of NF-κB in this process. The human esophageal squamous cancer cell line ECA109 was treated with GSPE (0-80 μg/mL) and BAY11-7082 (10 μmol/L) for 12, 24, and 48 h. The MTT assay was used to determine cell proliferation; alterations in cell apoptosis were detected by flow cytometry; levels of inflammatory factors interleukin-6 and cyclooxygenase-2 and apoptotic proteins Bax/Bcl-2 were measured by ELISA; qRT-PCR and western blots were used to examine the activation of caspase-3 and NF-κB signaling. GSPE inhibited the proliferation of ECA109 cells and induced cellular apoptosis in a time- and dose-dependent manner. ELISA results showed that GSPE and BAY11-7082 reduced the secretion of inflammatory cytokines interleukin-6 and cyclooxygenase-2. The results of PCR and western blotting indicated that GSPE and BAY11-7082 activated caspase-3 and attenuated the activation of the NF-κB signaling pathway. GSPE induced apoptosis in ECA109 cells and inhibited ECA109 cell proliferation via a reduction in the secretion of inflammatory cytokines. This mechanism may be related to the attenuation of NF-κB activity and the sensitization of caspase-3.